2021
DOI: 10.3389/feduc.2020.607096
|View full text |Cite
|
Sign up to set email alerts
|

Do Preschoolers Align Their Preferences With Those of a Powerful Individual?

Abstract: Very early on, children understand the hierarchical dimension of the social environment and use a variety of cues to guess who has more power in an interaction. A crucial aspect of power perception lies in the evaluation of high-power and low-power individuals. The current study examined the evaluation of power by preschoolers through social influence. Past research has shown that preschoolers take social category information into account when expressing their preferences. In particular, they tend align their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A tentative explanation may be that girls are more likely than boys to identify power cues (Brey & Shutts, 2015), but the vast majority of boys and girls succeeded at the comprehension check. An alternative explanation for the gender effect may then come from previous (albeit mixed) evidence on the relationship between gender and preferences for dominance, with girls being less interested in powerful individuals than boys (Charafeddine et al, 2021). This, however, may further be moderated by the gender of high-power and low-power individuals, a factor that was not manipulated in the present experiment.…”
Section: Resultsmentioning
confidence: 75%
“…A tentative explanation may be that girls are more likely than boys to identify power cues (Brey & Shutts, 2015), but the vast majority of boys and girls succeeded at the comprehension check. An alternative explanation for the gender effect may then come from previous (albeit mixed) evidence on the relationship between gender and preferences for dominance, with girls being less interested in powerful individuals than boys (Charafeddine et al, 2021). This, however, may further be moderated by the gender of high-power and low-power individuals, a factor that was not manipulated in the present experiment.…”
Section: Resultsmentioning
confidence: 75%
“…As a part of understanding the societies that they live in, children actively think about these inequalities, seeking to explain why things are structured the way they are and forming judgments about the consequences (Elenbaas et al, 2020). Recent research has revealed that children think about social relationships in terms of social power (Charafeddine et al, 2021;Gülgöz & Gelman, 2017) and status hierarchies (Yee et al, 2022). Thinking about power and status however does not convey whether children think these relationships are legitimate or unfair.…”
Section: Early Origins: How Children Perceive and Evaluate Social Ine...mentioning
confidence: 99%